Identification of textile fibers - Houck, Max M.; ScienceDirect eBooks (Cambridge : Woodhead Publishing Ltd, 2009)
This book provides a review of how textile fibers can be identified, both in the context of forensic science and within the textile industry. This is an important text for forensic scientists, police and lawyers who may be involved with the use of textile fibers to provide evidence in criminal cases. The identification of fibers is important to the textile industry, forensic science, fashion designers and historians among others. Identifying fibers involves observing the physical and chemical properties of the fiber for which there are a wide diversity of instruments available. This book provides a comprehensive review of fiber structure, the diversity of instruments available to identify fibers and applicications for a range of industries. The first part of the book examines the main fibers, their structure and characteristics. Part two focuses on methods of fiber identification, ranging from microscopic to DNA analysis. Specific applications, including how textiles are identified in forensic investigations. Identification of textile fibers is an important text for forensic scientists, police and lawyers who may be involved with the use of textile fibers to provide evidence in criminal cases. It will also be relevant for textile designers, technologists and inspectors wishing to assess fiber quality and understand fiber damage.
Part 1 Textile fiber structure and characteristics: Introduction to textile fiber identification-- Ways of identifying textile fibers and materials-- Natural animal textile fibers: structure, characteristics and identification-- Synthetic textile fibers: structure, characteristics and identification-- High performance fibers: structure, characteristics and identification-- The use of classification systems and production methods in identifying manufactured textile fibers. Part 2 Methods of fiber identification: Optical microscopy for textile fiber identification-- The use of spectroscopy for FP textile fiber identification-- Microspectrophotometry for textile fiber colour measurement-- Alternative and specialised textile fiber identification tests-- Analysis of dyes using chromatography-- DNA analysis in the identification of animal fibers in textiles. Part 3 Applications: Identifying plant fibers in textiles: the case of cotton-- The forensic identification of textile fibers-- Identifying and analysing of textile damage in the textile industry-- The role of fibre identification in textile conservation.
Max Houck is the Director of the Forensic Science Initiative and Director of Forensic Business Development at West Virginia University. He has published numerous articles and several books in related fields and serves on the editorial boards of the Journal of Forensic Sciences and the Journal of Forensic Identification.
Includes bibliographical references and index.
Elsevier
Keywords: Textile fibers; Textile fibers -- Identification; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; TECHNOLOGY & ENGINEERING -- Textiles & Polymers; Textile fibers; Electronic books